Ethnobiology teaching in distance education as evaluated by the students (UNED Research Journal, 2019)
Introduction: ethnobiology as interdisciplinary science has had an important development in recent few decades in Latin America. In Costa Rica, the career of Natural Resource Management by State Distance University (UNED) is the only career that offers an Ethnobiology course at undergraduate level by a virtual mode. Objective: identify the strengths and weaknesses of the teaching of ethnobiology in Costa Rica through a virtual model of distance education; from the perception of undergraduate students of the Natural Resources Management career of the UNED in the 2015 and 2016 cohorts. Methods: the perception and quality of materials and educational resources applied were evaluated by 20 students belonging to the 2015 and 2016 cohorts through a survey. Results: I found that most of the students considered the subject highly positive in their academic education. The student was agreed that the use of ethnobiological tools is an important element in identification, classification of use and management of the natural resources by the communities and it can contribute to the conservation of those resources. Conclusion: However, ethnobiology is poorly incorporated into management programs in Costa Rica due to the limited knowledge of its application, not only in areas with indigenous populations, but in urban regions.
Keywords: ethnobiology; education; distance education model; perception; biodiversity; culture